RANCANG BANGUN PORTAL KOMUNITAS FOTOGRAFI (FOTOYUK COMMUNITY) BERBASIS WEBSITE - Mochammad Sigit Dharmawan, - (2019)
This study discusses how photographers who have a photography community or for beginners to get to know photography. Photography itself was originally interpreted as an art by photographers, but over time began to enter new technologies and new knowledge that made photography increasingly developed towards a more modern one. Adapting to a community applies photo hunting, sharing, shared learning, interaction processes in groups from input to output such as the results of learning until it can be feed-back. Communication patterns can be seen from a communication process that occurs and takes place constantly or continuously. This research also provides a gallery whose function is to share photos of what they have captured by devices that can record images such as digital cameras, cellphone cameras, or DSLR cameras (Digital Single Lens Reflex).The development in this research uses Prototyping method which consists of 3 stages, Listen to customer requirements, Build / received mock-ups, Customer test mockups. This system is implemented using the PHP programming language, for the database using MySQL Server and the data is analyzed using PIECES. From the results of the use of research, the use of technology such as web-base makes it easy to find a community of photography, information about photography, photography galleries, and buying and selling photography tools, because of that this application is made to make it easier for people to do these activities.